1989
DOI: 10.3171/jns.1989.71.6.0805
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of unoperated intracranial arteriovenous malformations: study of 50 cases

Abstract: The clinical course of 50 patients with conservatively treated intracranial arteriovenous malformations (AVM's) was followed, most of them for more than 5 years. The average follow-up period was 13.4 years. The initial symptom was intracranial bleeding in 29 patients (58%) and seizure in 15 patients (30%). Small and deep-seated AVM's were associated with a high incidence of bleeding; however, repeated hemorrhages were not necessarily indicative of a poor prognosis. Children younger than 15 years had a better p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
1
9

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(99 citation statements)
references
References 20 publications
4
84
1
9
Order By: Relevance
“…6,13,14,16,40 Furthermore, recent studies of Halim et al, 14 Yamada et al, 40 da Costa et al, 6 and Hernesniemi et al 15 have shown relatively elevated annual rehemorrhage rates of 5-6% up to 5 years after an initial hemorrhagic presentation.…”
Section: Risk Factors For Hemorrhagementioning
confidence: 99%
“…6,13,14,16,40 Furthermore, recent studies of Halim et al, 14 Yamada et al, 40 da Costa et al, 6 and Hernesniemi et al 15 have shown relatively elevated annual rehemorrhage rates of 5-6% up to 5 years after an initial hemorrhagic presentation.…”
Section: Risk Factors For Hemorrhagementioning
confidence: 99%
“…There is a high propensity (80%) for the AVM childhood to present bleeding 8 , what is higher than that reported for adults 9,[15][16][17] . Likewise, epilepsy was reported in 12-18%of the AVM` s children series 7,18 and in 16 to 53% of the adult patients 19,20 .…”
Section: Discussionmentioning
confidence: 44%
“…Various factors have been proposed to playa role in the pathogenesis of spontaneous resolution of AVMs. These include haemorrhagic presentation with haematoma compression of the nidus of AVM or lesional thrombosis [5].…”
Section: Discussionmentioning
confidence: 99%